Risk of malignancy on suspicion of polyps in menopausal women. (September 2017) - Bel, Sandra; Billard, Camille; Godet, Julien; Viviani, Victor; Akladios, Cherif; Host, Aline; Faller, Emilie; Boisrame, Thomas; Hummel, Michel; Baldauf, Jean-Jacques; Lecointre, Lise; Garbin, Olivier
Abstract: Improved performances in gynaecological ultrasonography have enabled an increasing number of often asymptomatic endometrial polyps to be detected. Most of these polyps are removed surgically, as a precautionary measure, so as not to miss a case of endometrial cancer. Nonetheless, this management strategy is based solely on the sonographer's judgement and a number of these operations, which are probably of no benefit, could be avoided. In order to do so, risk factors for malignancy need to be identified. Objective: Estimate the prevalence of lesions in menopausal patients with a pre-operative diagnosis of endometrial polyp. Establish risk factors for malignancy. Study design: This is a single-centre retrospective study. Enrolment criteria were menopausal patients aged over 45 who had undergone hysteroscopic resection of a polyp. Pre-op diagnosis was made either by ultrasonography or diagnostic hysteroscopy. Malignant lesions included cancers and atypical hyperplasia. Benign lesions consisted of simple polyps, non-atypical simple hyperplasia and non-atypical complex hyperplasia. Risk factors studied were existing abnormal uterine bleeding, endometrial thickness, personal or first-degree family history of gynaecological cancer (breast, cervix, endometrium, ovary) and age on diagnosis. Results: 631 patients were enrolled of whom 30 presented a malignant disorder (4.75%); 579 patients (91.76%) presented a simple polyp, 11 a non-atypical simple hyperplasia (1.74%) and 11 a non-atypical complex hyperplasia (1.74%). On univariate analysis age alone proved to be statistically significant (OR 1.05; 95%CI = [1.02–1.09] p < 0.01), with a threshold of 59 years of age on the ROC curve. On multivariate analysis, factors predictive of a malignant lesion were age (OR = 1.06; 95%CI [1.02–1.10]), existence of AUB (OR = 2.4; 95% CI [1.07–5.42]) and family history (OR = 2.88; 95%CI [1.08–7.67]). Neither the univariate nor multivariate model was able to demonstrate a statistically significant relationship with respect to endometrial thickness. The risk of malignancy was 12.3% in patients aged over 59 presenting AUB. For all other subgroups, the risk varied between 2.31 and 3.78%. Conclusion: The risk of a malignant lesion appears to be high (12%) in menopausal patients aged over 59 presenting an endometrial polyp detected when there is pre-existing AUB. In this situation, hysteroscopic resection of endometrial polyps should therefore be routinely proposed. For other patients, the risk of a malignant lesion is low but not insignificant, standing at about 3%. Each patient record should therefore be discussed on an individual case basis, taking into consideration the patient's pre-existing conditions, after providing clear and appropriate information.